Method for producing polyferric chloride by microchannel reactor

The gas-liquid mixing and oxidation reaction is strengthened through the microchannel reactor, which solves the problems of long reaction time, low conversion rate and large equipment footprint in the production of polymer ferric chloride, and achieves efficient and stable water treatment agent production.

CN120398130AInactive Publication Date: 2025-08-01JIANGSU FUQING ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510717681.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-08-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing production process of polymer ferric chloride has problems such as long reaction time, low conversion rate, poor gas-liquid mixing efficiency, large equipment area, limited selection of oxidant and unstable products, making it difficult to meet the production needs of high-efficiency water treatment agents.

Method used

The microchannel reactor is used to mix and oxidize the ferrous chloride solution and the catalyst, and the gas-liquid mass transfer is strengthened through the microchannel geometry, combined with oxygen as an oxidant, and the reaction conditions are controlled to achieve rapid oxidation and polymerization. The subsequent maturation treatment is carried out to produce highly efficient polymerized ferrous chloride.

Benefits of technology

It significantly shortens the reaction time, improves the conversion rate to 99.95%, reduces the equipment area, achieves continuous production, excellent product flocculation performance, and stable water treatment effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120398130A_ABST
    Figure CN120398130A_ABST
Patent Text Reader

Abstract

The invention discloses a method for producing polyferric chloride by a microchannel reactor, and belongs to the field of water treatment agent polymerization. The method comprises the following steps: dissolving ferrous chloride, mixing the dissolved ferrous chloride with a catalyst in a premixer, introducing the mixture into a micro-channel reactor to carry out oxidation reaction with oxygen, and then polymerizing and curing to obtain the product. In the process, the gas-liquid ratio is controlled to be 1: 100, the oxidation temperature is 30-60 DEG C, the reaction time is 5-10 minutes, the polymerization temperature is 60-100 DEG C, and the pressure is 0.1-5 MPa. Compared with a traditional gap type reaction kettle process, the problems of long reaction time, low conversion rate and large occupied area of equipment are solved by utilizing the high mass transfer characteristic (the mass transfer coefficient is 3000-9000a / m < 2 >. M <-3 >) of the microchannel reactor, continuous and miniaturized production is realized, the product flocculation effect is good, the treated water is not subjected to color reversion, and high efficiency, environmental protection and economical efficiency are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment agents, and particularly to a method for producing polyferric chloride in a microchannel reactor. Background Art

[0002] At present, the production of polyferric chloride mainly adopts the batch reactor process. Using ferrous chloride solution, oxygen (or chlorine, hydrogen peroxide and other oxidants) and 20% sodium nitrite solution as raw materials, the materials are introduced into the non-stirred reactor by pump circulation, and gas-liquid mixing is realized by using an internal spray head. The reaction time is usually not less than 3 hours, the conversion rate is about 99.0%, and the product needs subsequent treatment. In this process, oxidants such as chlorine have strong toxicity, high cost or pollution problems. When using oxygen, the reaction is slow due to low mass transfer efficiency. Moreover, the traditional equipment covers an area of 300 square meters and it is difficult to adapt to the treatment requirements of ferrous chloride liquid with different yields.

[0003] The existing process has defects such as long reaction time, low conversion rate (only 99.0%), poor gas-liquid mixing efficiency (low mass transfer coefficient), large equipment floor area and difficult to move, and cannot realize continuous and miniaturized production. At the same time, the selection of oxidants is limited (such as chlorine is easy to leak, and the oxidation efficiency of hydrogen peroxide is low), resulting in high content of divalent iron in the product, unstable flocculation effect, easy color return of the treated water body, and it is difficult to meet the production requirements of high-efficiency water treatment agents. Utility Model Content

[0004] To solve the above technical problems, the present invention provides a method for producing polyferric chloride in a microchannel reactor with short reaction time, high conversion rate, high gas-liquid mixing efficiency, small equipment floor area and easy to move, which can realize continuous and miniaturized production.

[0005] A method for producing polyferric chloride in a microchannel reactor of the present invention includes the following steps: S1: Dissolve ferrous chloride in water to obtain a ferrous chloride solution; S2: Mix the ferrous chloride solution with a catalyst solution in a pre-mixer to form a mixed solution; S3: Introduce the mixed solution and oxygen into the microchannel reactor, and control the gas-liquid ratio and temperature for oxidation reaction; S4: After the oxidation reaction, carry out a polymerization reaction, and control the temperature and pressure; S5: After the polymerization reaction, carry out a ripening treatment to obtain polyferric chloride.

[0006] Further, in step S1, the iron content of the ferrous chloride solution is 13.5 - 14.0%, and the acidity is 3.0 - 3.5%. When dissolving ferrous chloride in water, mechanical stirring or magnetic stirring is used, the stirring rate is 200 - 300 revolutions per minute, the dissolution temperature is controlled at 20 - 40°C, and the dissolution time is 1 - 2 hours to ensure complete dissolution of ferrous chloride, obtaining a ferrous chloride solution with an iron content of 13.5 - 14.0% and an acidity of 3.0 - 3.5%. Monitor the solution temperature during the stirring process to avoid local overheating caused by exothermic dissolution.

[0007] Further, in step S2, the catalyst is a 5 - 25% aqueous solution of sodium nitrite, and the mass ratio of the ferrous chloride solution to the catalyst solution is 100:1.5.

[0008] Further, in step S2, the premixer is used to enhance mixing, so that the mixed liquid is dispersed evenly and then enters the microchannel reactor. The premixer is a static mixer or a dynamic stirring mixer. When a static mixer is used, a spiral mixing element is arranged inside, and turbulence is formed when the mixed liquid passes through, so that the ferrous chloride solution and the aqueous solution of sodium nitrite are quickly and evenly mixed, and the dispersion particle size of the mixed liquid is controlled at ≤50 μm to ensure the mass transfer uniformity before entering the microchannel reactor.

[0009] Further, in step S3, the oxygen purity ≥90%, the gas - liquid volume ratio is 1:100, the oxidation reaction temperature is 30 - 60°C, and the reaction time is 5 - 10 minutes.

[0010] Further, in step S3, the pressure of the microchannel reactor is controlled at 0.1 - 5 MPa, and preferably 0.5 MPa in the oxidation stage.

[0011] Further, in step S4, the polymerization reaction temperature is 60 - 100°C, the pressure is 0.1 - 5 MPa, and the reaction proceeds until the pH value of the system stabilizes at 1.5 - 2.5. During the polymerization reaction stage, the pH value of the system is monitored in real - time by an online pH sensor. When the pH value gradually rises from the initial 1.0 - 1.5 to 1.5 - 2.5 and stabilizes, it is determined that the polymerization reaction is completed. The pH value can be adjusted by dropping dilute hydrochloric acid or sodium hydroxide solution in this stage to ensure that the hydrolysis - polymerization reaction equilibrium shifts in the direction of generating polynuclear complexes, improving the flocculation performance of the product.

[0012] Further, in step S5, the temperature of the aging treatment is 20 - 40°C, the time is 12 - 24 hours, the stirring rate during the aging process is 50 - 100 revolutions per minute, the aging treatment is carried out in a closed stainless - steel container, and the inner wall of the container is coated with a polytetrafluoroethylene anti - corrosion layer, with a stirring rate of 50 - 100 revolutions per minute to avoid air entry affecting the product stability. Regularly take samples to detect the viscosity change during the aging process. When the viscosity reaches 5 - 10 cP, it is determined that the aging is completed, and a stable polyferric chloride product is obtained.

[0013] Furthermore, the microchannel reactor is selected to meet the following requirements: The inner diameter of the channel is 50-500 μm; Gas-liquid mass transfer coefficient is 3000-9000a / m 2 ·m -3 ; The material is 316L stainless steel or Hastelloy.

[0014] Furthermore, the feeding mode of the microchannel reactor is continuous feeding, and the flow rate of the ferrous chloride solution and the catalyst mixture is controlled by a metering pump to be 5-10 liters / minute, and the oxygen flow rate is controlled by a gas mass flow meter to keep the gas-liquid volume ratio stable at 1:100.

[0015] Accuracy requirements for metering pumps and gas mass flow meters In the continuous feeding system, the flow accuracy of the liquid metering pump is ±1% and the repeatability is ±0.5%. A plunger pump or diaphragm pump is used to ensure that the ferrous chloride and catalyst mixture is stably delivered at a flow rate of 5-10 liters / minute. The oxygen flow rate is controlled by a thermal gas mass flow meter with a measurement accuracy of ±1.5% of the full scale. A back pressure valve is used to maintain the pressure in the microchannel reactor stable at 0.1-5 MPa (preferably 0.5 MPa during the oxidation stage).

[0016] Temperature control scheme for microchannel reactor The reactor is equipped with a jacketed thermostat, which uses thermal oil or water circulation to control the temperature within an accuracy of ±1°C. During the oxidation reaction, the temperature is maintained at 30-60°C. A PID controller adjusts the jacket heat source in real time based on the feed temperature to prevent temperature fluctuations exceeding ±2°C due to reaction exotherm.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. Improved reaction efficiency: The microchannel reactor significantly shortens the reaction time and achieves rapid oxidative polymerization, greatly improving production efficiency compared to traditional processes.

[0018] 2. Mass transfer and mixing optimization: Utilize microchannel geometry to enhance gas-liquid mass transfer, increase contact area, make the reaction mixing more uniform and sufficient, and increase the oxidation reaction rate.

[0019] 3. Equipment and process advantages: The equipment occupies a significantly smaller area, is easy to move and can adapt to the processing needs of ferrous chloride with different outputs, while supporting continuous production.

[0020] 4. Advantages of oxidants: Oxygen is used as the oxidant, which is stable, economical and efficient, and avoids the pollution and safety hazards of toxic and harmful oxidants.

[0021] 5. Product performance optimization: The prepared polyferric chloride has excellent flocculation performance, the treated water body does not return to color, and the product has low impurity content and strong stability. Description of the Drawings

[0022] Figure 1 is the process implementation flowchart of the present invention; Detailed Implementation Modes The following combines the drawings and embodiments to further describe in detail the specific implementation modes of the present utility model. The following embodiments are used to illustrate the present utility model, but are not used to limit the scope of the present utility model.

[0023] It should be noted that when an element is referred to as "fixed to" another element, it can be directly on the other element or there may also be a central element. When an element is considered to be "connected" to another element, it can be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are only for the purpose of illustration and do not represent the only implementation mode.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which the present utility model belongs. The terms used in the description of the present utility model are only for the purpose of describing specific embodiments and are not intended to limit the present utility model. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0025] As Figure 1 shown, I. Embodiment 1. Embodiment 1 (standard process parameters) Raw material preparation: Ferrous chloride solution: iron content 13.8%, acidity 3.2%, 50 kg; Catalyst: 0.75 kg of 20% sodium nitrite aqueous solution; Oxygen: purity 90%.

[0026] Process steps: Dissolution: Ferrous chloride is dissolved in water, mechanically stirred (250 revolutions per minute), dissolved at 30 °C for 1.5 hours to obtain a solution; Premixing: Mixed with 20% sodium nitrite solution in a static mixer (spiral element), the dispersion particle size ≤ 50 μm; Oxidation: The mixed solution enters the microchannel reactor (inner diameter 200 μm, 316L stainless steel, mass transfer coefficient 5000 a / m 2 ·m -3), oxygen is introduced at a gas-liquid ratio of 1:100, and the reaction is carried out at 40 °C and 0.5 MPa for 5 minutes; Polymerization: The temperature is raised to 80 °C, 0.5 MPa is maintained, and the reaction stops when the pH value stabilizes at 2.0; Aging: Stirring is carried out in a closed state at 30 °C (60 revolutions per minute) for 18 hours, and the viscosity reaches 6 cP.

[0027] Product data: Conversion rate: 99.95%; Ferrous iron: 0.02%; Acidity: 0.08%; Flocculation effect: The water body is clear and does not turn color.

[0028] 2. Example 2 (Optimization of microchannel inner diameter) Differential parameters: Inner diameter of microchannel: 50 μm, mass transfer coefficient 9000 a / m 2 ·m -3 ; Oxidation reaction time: 5 minutes; Other conditions are the same as in Example 1.

[0029] Product data: Conversion rate: 99.96%; Ferrous iron: 0.015%; Acidity: 0.06%; Remark: The flow rate is limited but the mass transfer efficiency is higher.

[0030] 3. Example 3 (Optimization of aging time) Differential parameters: Aging time: 24 hours, temperature 25 °C, stirring rate 80 revolutions per minute; Other conditions are the same as in Example 1.

[0031] Product data: Conversion rate: 99.95%; Ferrous iron: 0.01%; Viscosity: 8 cP; Stability: No precipitation after 3 months of storage.

[0032] II. Comparative example 1. Comparative example 1 (Traditional batch reactor) Process parameters: Equipment: 500 L reactor (without stirring), spray head mixing; Reaction time: 180 minutes, 30 °C, 0.1 MPa; Amount of raw materials: The same as in Example 1, 1.25 kg of catalyst.

[0033] Product data: Conversion rate: 99.0%; Ferrous iron: 0.72%; Acidity: 0.18%; Floor area: 300 m².

[0034] 2. Comparative Example 2 (microchannel but parameters not optimized) Differential parameters: Oxidation reaction pressure: 0.1 MPa, reaction time: 180 minutes; Other conditions are the same as in Example 2.

[0035] Product data: Conversion rate: 99.3%; Ferrous iron: 0.29%; Acidity: 0.04%; Remark: The high mass transfer advantage of the microchannel is not exploited.

[0036] III. Data comparison table

[0037] IV. Summary Efficiency improvement: By using a microchannel reactor, the present invention shortens the reaction time from 3 hours in the traditional process to 5 - 10 minutes, with the efficiency increased by 30 times, and the mass transfer coefficient (3000 - 9000 a / m 2 ·m -3 ) is much higher than that of traditional equipment.

[0038] Conversion rate and product quality: The conversion rate reaches over 99.95%, the ferrous iron content is ≤ 0.02%, the acidity is ≤ 0.08%, the flocculation effect is significant and the treated water does not turn color, which is superior to the traditional process.

[0039] Advantages of equipment and process: The floor area is reduced to 60 m², realizing skid-mounted modularization; continuous feeding with precise metering (the accuracy of the metering pump is ±1%) ensures the process stability and solves the problems of large size and cumbersome operation of traditional process equipment.

[0040] Parameter sensitivity: The comparative examples prove that the microchannel process needs to match parameters such as pressure (0.5 MPa is preferred) and reaction time to fully exert the advantage of high mass transfer efficiency, verifying the necessity of parameter optimization in the present invention.

[0041] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the technical principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for producing polymeric ferric chloride in a microchannel reactor, characterized in that, It includes the following steps: S1: Dissolve ferrous chloride in water to obtain a ferrous chloride solution; S2: Mix the ferrous chloride solution with a catalyst solution in a premixer to form a mixed solution; S3: Introduce the mixed solution and oxygen into a microchannel reactor, and control the gas-liquid ratio and temperature for an oxidation reaction; S4: After the oxidation reaction, carry out a polymerization reaction, controlling the temperature and pressure; S5: After the polymerization reaction, carry out a ripening treatment to obtain polyferric chloride.

2. The method for producing polymeric ferric chloride by using a microchannel reactor according to claim 1, characterized in that, In step S1, the iron content of the ferrous chloride solution is 13.5 - 14.0%, and the acidity is 3.0 - 3.5%.

3. The method for producing polymeric ferric chloride by using a microchannel reactor according to claim 1, characterized in that, In step S2, the catalyst is a 5 - 25% aqueous solution of sodium nitrite, and the mass ratio of the ferrous chloride solution to the catalyst solution is 100:1.

5.

4. The method for producing polymeric ferric chloride by using a microchannel reactor according to claim 3, characterized in that, In step S2, the premixer is used to strengthen the mixing, so that the mixed solution is dispersed evenly and then enters the microchannel reactor.

5. The method for producing polymeric ferric chloride in a microchannel reactor according to claim 1, characterized in that, In step S3, the oxygen purity is ≥90%, the gas-liquid volume ratio is 1:100, the oxidation reaction temperature is 30 - 60°C, and the reaction time is 5 - 10 minutes.

6. The method for producing polymeric ferric chloride by using a microchannel reactor as claimed in claim 5, wherein, In step S3, the pressure of the microchannel reactor is controlled at 0.1 - 5 MPa, and preferably 0.5 MPa in the oxidation stage.

7. The method for producing polymeric ferric chloride by using a microchannel reactor according to claim 1, wherein In step S4, the polymerization reaction temperature is 60 - 100°C, the pressure is 0.1 - 5 MPa, and the reaction proceeds until the pH value of the system is stable at 1.5 - 2.

5.

8. The method for producing polymeric ferric chloride by using a microchannel reactor according to claim 1, wherein, In step S5, the temperature of the ripening treatment is 20 - 40°C, the time is 12 - 24 hours, and the stirring rate during the ripening process is 50 - 100 revolutions per minute.

9. The method for producing polymeric ferric chloride by using a microchannel reactor according to claim 6, wherein, The selection of the microchannel reactor meets the following requirements: The inner diameter of the channel is 50 - 500 μm; The gas-liquid mass transfer coefficient is 3000 - 9000 a / m 2 ·m -3 ; The material is 316L stainless steel or Hastelloy.

10. The method for producing polymeric ferric chloride by using the microchannel reactor according to claim 9, characterized in that, The feeding mode of the microchannel reactor is continuous feeding. The flow rates of the ferrous chloride solution and the catalyst mixture are controlled by a metering pump at 5 - 10 liters per minute, and at the same time, the oxygen flow rate is controlled by a gas mass flowmeter to keep the gas-liquid volume ratio stable at 1:100.